Composite nonwoven materials structure, properties and applications - Das, Dipayan; Pourdeyhimi, Behnam (Elsevier Science, 2014)
Composite nonwoven materials are versatile materials with a variety of applications, including hygiene, medicine and filtration. This important book provides a technical resource for professionals and academics in the field. It explores these materials in terms of fiber types used, manufacturing processes, structure, and physical properties
Keywords: TECHNOLOGY & ENGINEERING / Engineering (General); TECHNOLOGY & ENGINEERING / Reference; Composite materials; Nonwoven fabrics; Verbundwerkstoff; Vliesstoff